The first four years - Wilder, Laura Ingalls (London : Puffin, 1973)
During their first four years of marriage, Laura and Almanzo Wilder have a child on fight a losing battle in their attempts to succeed at farming on the South Dekota prairie.
Keywords: Frontier and pioneer life -- Fiction